2019
DOI: 10.1002/rcm.8481
|View full text |Cite
|
Sign up to set email alerts
|

Complementary approach for accurate determination of carbon isotopic compositions in γ‐hydroxybutyric acid using gas chromatography/combustion‐isotope ratio mass spectrometry

Abstract: Rationale γ‐Hydroxybutyric acid (GHB) is a naturally endogenous neurotransmitter that is popular as a recreational drug due to its sedative, hypnotic, and euphoric effects. GHB derived from endogenous production or exogenous ingestion has been effectively discriminated by carbon isotopic compositions (δ13C values) through gas chromatography/combustion‐isotope ratio mass spectrometry (GC/C‐IRMS). However, an unintended uncertainty of isotopic signatures caused by a wide range of GHB quantities remains unsolved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…2019 complementary approach for accurate determination of carbon isotopic compositions in gamma-hydroxybutyric acid using gas chromatography/combustion-isotope ratio mass spectrometry [ 118 ]; 2020 ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method for the simultaneous quantification of GHB, GBL, and 1,4-BD in four popular beverages, including carbonated drinks, tea, apple cider vinegar, and coffee [ 119 ]; H-1-NMR results of seven kinds of beverages spiked GBL indicated that were spiked with GBL where the GBL was transformed into GHB in six popular beverages under certain conditions which could happen during transportation and storage [ 120 ]; detection method based on DLLME and GC-MS/MS for GHB in beverages [ 121 ]; two new oxazole derivatives for detection of gamma-hydroxybutyric acid (GHB) in soft drinks and alcoholic beverages, by color and fluorescence changes [ 122 ]; review [ 123 ]; GC-MS analysis of GHB in energy drinks [ 124 ]; 2021 a total vaporization solid-phase microextraction (TV-SPME) method with GC-MS for the detection of GHB and GBL in alcoholic beverages [ 125 ]; review [ 126 ]; LLE-FTIR based method to GBL in adulterated beverages [ 127 ]; forensic routine cases were measured to consider the potential of additional GC-MS analysis for GHB related acids (3,4-dihydroxy butyric acid, 2,4-dihydroxy butyric acid and glycolic acid) [ 128 ]; colorimetric chemosensor for the real-time in situ detection of GHB in soft drinks and alcoholic beverages [ 129 ]; heteroditopic chemosensors for detecting GHB in soft drinks, alcoholic beverages and synthetic urine [ 130 ]; a colorimetric detection kit was developed to enable rapid GHB detection in beverages [ 131 ]; 2022 development of a fluorescence probe based on a cyanostilbene scaffold for the detection of GHB [ 132 ]; method for in situ colorimetric GHB detection using various self-protection products coated with 2-(3-bromo-4-hydroxystyryl)-3-ethylbenzothiazol-3ium iodide (BHEI) as a chemical receptor embedded in hydrogels [ 133 ].…”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%
“…2019 complementary approach for accurate determination of carbon isotopic compositions in gamma-hydroxybutyric acid using gas chromatography/combustion-isotope ratio mass spectrometry [ 118 ]; 2020 ultra-high-performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) method for the simultaneous quantification of GHB, GBL, and 1,4-BD in four popular beverages, including carbonated drinks, tea, apple cider vinegar, and coffee [ 119 ]; H-1-NMR results of seven kinds of beverages spiked GBL indicated that were spiked with GBL where the GBL was transformed into GHB in six popular beverages under certain conditions which could happen during transportation and storage [ 120 ]; detection method based on DLLME and GC-MS/MS for GHB in beverages [ 121 ]; two new oxazole derivatives for detection of gamma-hydroxybutyric acid (GHB) in soft drinks and alcoholic beverages, by color and fluorescence changes [ 122 ]; review [ 123 ]; GC-MS analysis of GHB in energy drinks [ 124 ]; 2021 a total vaporization solid-phase microextraction (TV-SPME) method with GC-MS for the detection of GHB and GBL in alcoholic beverages [ 125 ]; review [ 126 ]; LLE-FTIR based method to GBL in adulterated beverages [ 127 ]; forensic routine cases were measured to consider the potential of additional GC-MS analysis for GHB related acids (3,4-dihydroxy butyric acid, 2,4-dihydroxy butyric acid and glycolic acid) [ 128 ]; colorimetric chemosensor for the real-time in situ detection of GHB in soft drinks and alcoholic beverages [ 129 ]; heteroditopic chemosensors for detecting GHB in soft drinks, alcoholic beverages and synthetic urine [ 130 ]; a colorimetric detection kit was developed to enable rapid GHB detection in beverages [ 131 ]; 2022 development of a fluorescence probe based on a cyanostilbene scaffold for the detection of GHB [ 132 ]; method for in situ colorimetric GHB detection using various self-protection products coated with 2-(3-bromo-4-hydroxystyryl)-3-ethylbenzothiazol-3ium iodide (BHEI) as a chemical receptor embedded in hydrogels [ 133 ].…”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%